Succession of States and the War of the Pacific - Céspedes Proto, Rodrigo (Derecho Público Iberoamericano, 2022)
This paper examines the institution of international law called “succession of States”. First, it analyzes the cases of modification of obligations according to the private law doctrine. The contemporary doctrine of state succession and personal subrogation is then studied. Finally, two Chilean precedents that anticipate modern international law are examined.